2011
DOI: 10.1002/sd.429
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and determinants of environmental concern: the case of Hong Kong and its implications for sustainable development

Abstract: Environmental concern is a precursor to behavioural change. This article draws upon data from two surveys conducted in 2000 and 2008 to examine the development of environmental concern in Hong Kong and its major determinants. It fi nds that Hong Kong people have consistently shown a high level of environmental concern in terms of both their perception of the seriousness of environmental problems and their assessment of how these problems will develop in the future. In line with previous fi ndings, our study co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 20 publications
0
36
3
Order By: Relevance
“…The reasons for this analysis are twofold. One is that environmental concern is regarded as precursor to behavioral change (Wong and Wan 2011). The other is that behavior can be changed by making human beings more knowledgeable about the environment and its associated issues (Hungerford and Volk 1990).…”
Section: Environmental Education Researchmentioning
confidence: 98%
“…The reasons for this analysis are twofold. One is that environmental concern is regarded as precursor to behavioral change (Wong and Wan 2011). The other is that behavior can be changed by making human beings more knowledgeable about the environment and its associated issues (Hungerford and Volk 1990).…”
Section: Environmental Education Researchmentioning
confidence: 98%
“…Through a review of literature, it has been found that organizations having more female workforce exhibit higher levels of corporate social responsibility engagements such as social work and environmental projects (Williams, 2003;Setó-Pamies, 2015;Fernandez-Feijoo, Romero, & Ruiz-Blanco, 2014). Women are more concerned about moral and social issues such as sustainability and environmental conservation and thus, engage more frequently in eco-friendly behavior than men (Wong & Wan, 2011). Moreover, whereas women more commonly exhibit voluntary behaviors like those involved in corporate charitable activities, men mostly focus on economic and material aspects within the organization (Ibrahim & Angelidis, 1994;Smith, Wokutch, Harrington, & Dennis, 2001).…”
Section: Gender As a Moderatormentioning
confidence: 99%
“…Burton and Hegarty (1999) have concluded that women have higher expectations of CSR than men. Women have a higher concern for ethical issues such as the environment and thus tend to engage more frequently in environmentally friendly behavior than men (Davidson and Freudenburg, 1996;Wong and Wan, 2011). Similarly, while women tend to relate to discretionary behavior of the type involved in corporate charitable activities, their male counterparts are more likely to focus on economic and instrumental concerns within the organization (Smith et al, 2001;Ibrahim and Angelidis, 1994).…”
Section: Literature Review Gender Differences In Csr Perceptionsmentioning
confidence: 99%
“…In the same vein, Vitell et al (1993) have proved that highly masculine people seek superior performance at the expense of ethical codes since they are more ambitious and performance-oriented. On the other hand, while women tend to hold pro-environment beliefs, they are nonetheless more likely to have a negative view of environmental performance than men (Wong and Wan, 2011). Therefore, masculinity is negatively related to one's susceptibility to corporate ethics, and consumer trust in a company's unethical context is more likely to be lower in the case of women rather than men (Yoo and Donthu, 2002).…”
Section: Csr To Corporate Distrustmentioning
confidence: 99%